Analisis Kepuasan Konsumen Terhadap Pembelian Sayuran Di Swalayan - Indaryati, Sri; Zulkarnain, Zulkarnain; Andini, Lorenza Dwi (Penerbit Goodwood, 2025)
Purpose (Purpose): This study aimed to analyze the level of consumer satisfaction with fresh vegetables at Chandra Superstore Metro, with the output of consumers understanding that the price of fresh vegetables is in accordance with the benefits contained in fresh vegetables. Method (Method): This study was conducted intentionally (purposive sampling) with the criteria of consumers who purchased vegetables more than three times and were over 17 years of age. Primary data sources were obtained from consumer interviews using questionnaires, while secondary data were obtained from book literature, previous research, and other related agencies. Primary data sources were obtained from the results of consumer interviews using questionnaires, while secondary data were obtained from book literature, previous research, and other related agencies. Results (Results): The results of the level of consumer satisfaction with fresh vegetables at Chandra Superstore Metro were classified as very satisfied, with a Customer Satisfaction Index (CSI) calculation value of 86.93. Conclusion: Consumers are highly satisfied (CSI 86.93%); however, improvements are needed in product assurance, transaction speed, and complaint handling. Limitations: The limitations of this study are that the time period and duration of vegetable purchases by consumers do not use a specific time limit, repeat purchases by consumers are still not apparent, and the number of samples needs to be increased. Contribution: This study contributes to science by providing education to consumers about the benefits of fresh vegetables at relatively high prices. Contribution of knowledge to fresh vegetable provider companies to implement supporting factors for consumer satisfaction to maintain the performance of providing fresh vegetables.